The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.1007/978-3-540-69139-6_57
|View full text |Cite
|
Sign up to set email alerts
|

NN-Based R-peak Detection in QRS Complex of ECG Signal

Abstract: -eural Network (NN) is designed to detect QRS complex from ECG signal. QRS complex detection is essential so that RR-interval can be measured for disease classification and can also be monitoring the heart rate. In this paper, a supervised Neural Network based algorithm has been used to detect R in QRS complex. It was tried to find out the R-peak in QRS complex with missing peak and false peak as well, so that the correct decision can be made by the physician and clinician. The accuracy of finding the R-peak b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…These works suffer mainly from two limitations: their sensitivity to noise and the choice of a threshold. Other works exploit nonlinear analysis methods, especially the neural networks [5,6] and non-stationary analysis tools such as wavelets that are the most used [7,8,9]. Particularly in [7], for the QRS complex detection by Discreet Wavelet Transform, The authors have used different mother wavelets: Cubic Spline, Haar and Daubechies4 (Db4), where the choice of decomposition scale is empirical .They have shown that the best results are given by the Cubic Spline and the Db4 wavelets.…”
Section: Introductionmentioning
confidence: 99%
“…These works suffer mainly from two limitations: their sensitivity to noise and the choice of a threshold. Other works exploit nonlinear analysis methods, especially the neural networks [5,6] and non-stationary analysis tools such as wavelets that are the most used [7,8,9]. Particularly in [7], for the QRS complex detection by Discreet Wavelet Transform, The authors have used different mother wavelets: Cubic Spline, Haar and Daubechies4 (Db4), where the choice of decomposition scale is empirical .They have shown that the best results are given by the Cubic Spline and the Db4 wavelets.…”
Section: Introductionmentioning
confidence: 99%